2022
DOI: 10.1155/2022/8996203
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Treatment with Activin and Hepatocyte Growth Factor Induces FOXM1 to Promote Colorectal Cancer Liver Metastasis

Abstract: Background. Cancer stem cells (CSCs) are involved in liver metastasis in colorectal cancer (CRC). Activin and hepatocyte growth factor (HGF) are important regulators of stem cell properties. This study was performed to explore the effect of activin and HGF on CRC invasion and metastasis. The key genes involved in the action of activin and HGF in CRC were identified. Methods. HCT116 CRC cells were sequentially treated with activin and HGF and examined for migration and invasion in vitro and liver metastasis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(51 reference statements)
0
2
0
Order By: Relevance
“… 17 In our previous study, we found that activin alone increased the messenger RNA and protein expression of FOXM1 through SMAD family member 2. 18 HGF alone enhanced the phosphorylation of FOXM1, without altering the total protein level of FOXM1. 18 Since activin and HGF have a capacity of promoting an aggressive phenotype in colorectal cancer cells, 18 - 20 we hypothesized that activin and HGF treatment might exert a positive effect on colorectal cancer stemness through FOXM1.…”
Section: Introductionmentioning
confidence: 85%
“… 17 In our previous study, we found that activin alone increased the messenger RNA and protein expression of FOXM1 through SMAD family member 2. 18 HGF alone enhanced the phosphorylation of FOXM1, without altering the total protein level of FOXM1. 18 Since activin and HGF have a capacity of promoting an aggressive phenotype in colorectal cancer cells, 18 - 20 we hypothesized that activin and HGF treatment might exert a positive effect on colorectal cancer stemness through FOXM1.…”
Section: Introductionmentioning
confidence: 85%
“…Hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) are some examples of molecules that can be elevated in the serum of CRC with liver metastasis [49,50].…”
Section: Serum Markers/liquid Biopsymentioning
confidence: 99%